A comparison of two treatment protocols in the management of exercise-associated postural hypotension: a randomised clinical trial. Issue 14 (28th June 2010) - Anley, Cameron; Noakes, Timothy; Collins, Malcolm; Schwellnus, Martin P
Abstract : Objective: To investigate which of two commonly used treatment protocols for exercise-associated postural hypotension (EAPH) resulted in earlier discharge from the medical facility. Methods: This randomised clinical field trial was undertaken at two Ironman Triathlon competitions and one ultra-distance footrace. All collapsed athletes admitted to the medical facilities were considered for the trial. Following clinical assessment and special investigations to confirm the diagnosis of EAPH, 28 athletes were randomly assigned to an oral fluid and Trendelenburg position (OT=14) or an intravenous fluid (IV=14) treatment group. Following admission fluid intake was recorded, and all athletes were assessed clinically (blood pressure, heart rate, level of consciousness) every 15 min until discharge criteria were met. The main measure of outcome was the time to discharge (min). Results: On admission, subjects in the OT and IV groups were similar with respect to age, systolic blood pressure, heart rate and serum sodium concentration. There were no significant differences in heart rate, systolic and diastolic blood pressure between groups and over time until discharge. The fluid intake during the treatment period was significantly greater in the IV group (IV 1045±185 ml, OT 204±149 ml; p<0.001). The average time to discharge for the OT group (58±23 min) was similar to that of the IV group (52.5±18 min; p=0.47). Conclusion: Endurance athletes with EAPH can be treated effectively using the Trendelenburg position and oral fluids and the administration of intravenous fluids does not reduce the time to discharge. The findings of this study support the hypothesis that EAPH is a result of venous pooling due to peripheral vasodilatation, rather than dehydration.